2011
DOI: 10.1111/j.1365-2966.2011.19202.x
|View full text |Cite
|
Sign up to set email alerts
|

On the progenitors of millisecond pulsars by the recycling evolutionary channel

Abstract: The recycling model suggested that low‐mass X‐ray binaries (LMXBs) could evolve into binary millisecond pulsars (BMSPs). In this work, we attempt to investigate the progenitor properties of BMSPs formed by the recycling evolutionary channel, and if submillisecond pulsars can be produced by this channel. Using Eggleton’s stellar evolution code, considering that the dead pulsars can be spun up to a short spin period by the accreting material and angular momentum from the donor star, we have calculated the evolut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…The main reason is that we have taken into account the effect of disk instability. The ΔM 1 distribution is roughly in line with Liu & Chen (2011), who found that ΔM 1 is generally less than 0.6 M in their calculations for systems with a 1.4 M NS and a 1.0-2.0 M donor star. Moreover, we find that systems with initially massive NSs (1.8 M ) may accrete enough mass to evolve into BMSPs with 60 days P orb 200 days, while light NSs in wide binaries are more likely to be partially recycled.…”
Section: The P Orb -M Wd Relation For Low-mass Bmspssupporting
confidence: 87%
See 1 more Smart Citation
“…The main reason is that we have taken into account the effect of disk instability. The ΔM 1 distribution is roughly in line with Liu & Chen (2011), who found that ΔM 1 is generally less than 0.6 M in their calculations for systems with a 1.4 M NS and a 1.0-2.0 M donor star. Moreover, we find that systems with initially massive NSs (1.8 M ) may accrete enough mass to evolve into BMSPs with 60 days P orb 200 days, while light NSs in wide binaries are more likely to be partially recycled.…”
Section: The P Orb -M Wd Relation For Low-mass Bmspssupporting
confidence: 87%
“…It is expected that the NS has to accrete mass of at least a few ∼0.01 M to reach a millisecond period, but this is difficult to achieve for NSs in wide binaries (see also Liu & Chen 2011) because the mass transfer rate (which increases with increasing orbital period) is likely to be super-Eddington and the accretion disk is likely to be unstable. In Figure 7, we show the mass transfer rate |Ṁ 2 | and the accreted mass ΔM 1 of the NS as a function of the final orbital period P orb .…”
Section: The P Orb -M Wd Relation For Low-mass Bmspsmentioning
confidence: 99%
“…The NS is subsequently spun-up to a high spin frequency via accretion of mass and angular momentum once the secondary star evolves (For a more detailed review, see i.e. Alpar et al (1982); Bhattacharya and van den Heuvel (1991); Tauris et al (2000); Liu and Chen (2011);Tauris (2011)) In this section we will determine the spin period of MSPs originated from WDs, the process begins with simple Keplerian frequency, the angular velocity of the NS is equal to the Keplerian angular velocity of the magnetosphere, at roughly the Alfvén surface,…”
Section: Spin Periodmentioning
confidence: 99%
“…Many studies have shown that the final state of a MSP strongly depends on the initial mass of its companion and the orbital separation (e.g. Tauris 2011;Liu & Chen 2011). Furthermore, evolutionary status of the compan-ion at the onset of the Roche lobe overflow (RLO) is suggested to be a key factor in determining the timescale of the mass transfer phase which can directly affect the nature of the MSP (Tauris 2011;Tauris & Savonije 1999).…”
Section: Correlation and Regression Analysismentioning
confidence: 99%